167k views
1 vote
Given 36 − 9, simplify the expression using the Difference of Squares.

Wait, wait. I know what you are saying. 36 − 9 is not exactly a difficult math problem, it is 27. Yes you are correct; however, 36 − 9 is going to serve as a proof that the Difference of Squares is valid regardless of what x and y are.

36 − 9

62 − 32

This looks exactly like the Difference of Squares, x2 − y2. So substitute 6 and 3 in for x and y.

User SlyChan
by
6.1k points

1 Answer

5 votes

Answer:

See below

Explanation:

Using formula

  • x^2 - y^2 = (x + y)(x - y)

Applying to given expression

  • 36 - 9 =
  • 6^2 - 3^2=
  • (6 + 3)(6 - 3)=
  • 9*3=
  • 27
User Ttarik
by
5.6k points